PERAN KEPUASAN KERJA DALAM HUBUNGAN KOMPENSASI DAN KINERJA PEGAWAI - Antari, Sili; Emiliana Beti Sopian; I Putu Santika (JUIMA : JURNAL ILMU MANAJEMEN, 2025)
This study aims to analyze the role of job satisfaction in the relationship between compensation and employee performance. The population in this study consisted of all employees of Karangasem I Public Health Center, totaling 59 individuals. The sampling technique used was a saturated sample or census technique, where the entire population was used as the sample, amounting to 59 respondents. The analysis techniques used in this research included validity tests, reliability tests, classical assumption tests, and path analysis. The results of the analysis show that: 1) Compensation has a positive and significant effect on job satisfaction; 2) Compensation has a positive and significant effect on employee performance; 3) Job satisfaction has a positive and significant effect on employee performance; 4) Compensation positively influences employee performance through job satisfaction at Karangasem I Public Health Center. The suggestion of this study is that the Head of Karangasem I Public Health Center is expected to improve compensation, enhance job satisfaction, and increase employee performance.